Logistic model of import of goods into the territory of the customs Union of Belarus, Kazakhstan and the Russian Federation - S. S. Ilyukhina (Путеводитель предпринимателя)
The article deals with the application of the tools of network models for the organization of processes in the movement of goods across the customs border of the Customs Union.